Influence of Time of Nitrogen Application on Productivity and Nitrogen Use Efficiency of Rain- fed Lowland Rice (Oryza sativa L.) in the Vertisols of Fogera plain, Northwestern Ethiopia - Assefa, A; Tadese, T; Liben, M (Ethiopian Journal of Science and Technology, 2025)
An experiment consisting of two fertilizer rates (69/10 and 46/20 kg N/P ha-1) and five nitrogen (N) application times (half at planting + half at tillering (control), half at planting + half at panicle initiation, one-third at planting + two-third at tillering, one-third at planting + two-third at panicle initiation and one-third at planting + one-third at tillering +one-third at panicle initiation) was conducted in factorial RCBD on the Vertisols of Fogera plain during the 2006 and 2007 cropping seasons. The objective of the experiment was to identify the best time of N application for maximum rain-fed lowland rice yield in the Fogera plain. Results showed significant difference in grain yield in response to the time of N application. The highest mean grain yield (4409 kg ha-1) was recorded when N was applied one-third at planting and two-third at the tillering stage of the crop. Nitrogen fertilizer rates and the interaction with its time of application showed non-significant differences for all parameters. The agronomic Nitrogen Use Efficiency (NUE) was found to be higher for one-third at planting and two-third at tillering nitrogen application compared to the other treatments. Hence, application of nitrogen one-third at planting and two-third at tillering stage of rice, irrespective of the fertilizer rate, is recommended for rice production in the Fogera plain.